Does cannabidiol reduce the adverse effects of cannabis in schizophrenia? A randomised, double-blind, cross-over trial - Chesney, Edward; Oliver, Dominic; Sarma, Ananya; Lamper, Ayse Doga; Slimani, Ikram; Lloyd, Millie; Dickens, Alex M.; Welds, Michael; Kråkström, Matilda; Gasparini-Andre, Irma; Oresic, Matej; Lawn, Will; et al. (Springer Nature, 2025)
In patients with schizophrenia, cannabis use exacerbates symptoms and can lead to a relapse of psychosis. Some experimental studies in healthy volunteers suggest that pre-treatment with cannabidiol (CBD) may reduce these effects, but others do not. Here, we investigated whether pre-treatment with CBD ameliorates the acute adverse effects of cannabis in patients with schizophrenia. Participants (n = 30) had schizophrenia or schizoaffective disorder plus a comorbid cannabis use disorder. In a double-blind, randomised, placebo-controlled, crossover trial, participants received oral CBD 1000 mg or placebo three hours before inhaling vaporised cannabis (containing Δ9-tetrahydrocannabinol (THC) 20-60 mg). The primary outcome was delayed verbal recall measured with the Hopkins Verbal Learning Test-Revised. We also measured psychotic symptoms with the Positive and Negative Syndrome Scale (PANSS) - positive subscale. Delayed verbal recall after cannabis administration was 3.5 words (95% confidence interval [CI]: 2.5-4.5) following pre-treatment with CBD, compared to 4.8 words (95% CI: 3.9 to 5.8) following pre-treatment with placebo (mean difference [MD] = -1.3 [95% CI: -2.0 to -0.6]; p = 0.001). After CBD pre-treatment, inhalation of cannabis was associated with an increase in PANSS-P score of 5.0 (95% CI: 3.6 to 6.5), compared to 2.9 (95% CI: 1.5 to 4.3) following pre-treatment with placebo (MD = 2.2 [95% CI: 0.6 to 3.7]; p = 0.01). Administration of CBD did not have a significant effect on plasma concentration of THC or its active metabolite, 11-hydroxy-THC. In patients with schizophrenia and a comorbid cannabis use disorder, pre-treatment with CBD did not attenuate the acute effects of cannabis on memory impairment or psychotic symptoms, but appeared to exacerbate them. The study was registered on Clinicaltrials.gov (NCT04605393).